Exploring the relationship between digital skills, online buying, and encountered problems across europe - Nina Angelovska Stankov (UTMS Journal of Economics, 2023)
In the evolving landscape of e-commerce, digital skills serve as a fundamental determinant of effective engagement, influencing the overall online purchasing experience and the ability to address encountered problems. This research, based on Eurostat data for 2021 across 36 European countries, employs quantitative methods, including correlations and regression, to explore the relationship between the level of digital skills, internet purchasing behavior, and the reporting of problems. The study reveals a positive correlation, indicating that a higher level of digital skills is associated with increased internet purchasing. Additionally, individuals with lower digital skills are more likely to refrain from reporting problems during online transactions. These findings offer valuable insights for practitioners and policymakers, highlighting the pivotal role of digital skills in fostering positive online interactions and shaping strategies for a seamless e-commerce experience.
Keywords: M30; 330; E-commerce; Problems encountered when buying online; Eurostat; Regression Analysis